Confucian value-based leadership communication: a study on Tun Dr. Mahathir Mohamad - Cheah, Joyce Lynn-Sze; Mohd. Khairie Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The study on leadership communication is one of the most often researched topics on leadership. However, there have been only a few studies focused on Confucian value-based leadership in a multicultural society. Therefore, this study is designed to develop a leadership communication model that works in an intercultural context. The aim of the study is twofold, first, is to identify the attributes of Dr. Mahathir’s vision formation and vision articulation associated with Confucian values, which focus on leadership communication; and second, is to provide a Confucian model of leadership that can be applied by multi-cultural leaders. This study analysed 37 speeches and interviewed 15 Chinese leaders. Findings reveal that Dr. Mahathir applied numerous attributes in developing his speech content, such as value-based cores, growth and ideological goals to capture his audience’s minds and hearts simultaneously. This study identifies three main attributes of Dr. Mahathir’s vision articulation; they include clarity, inspirational imagery and challenge. Five Confucian values which are relevant to the Chinese community and Dr. Mahathir’s leadership communication are also presented in this study. The Confucian values are Zhi (wisdom), Xin (trust), Xiao (filial piety), Ren (benevolence) and Zhong yong (moderation). This study also contributes to the expansion of the leadership communication research in Malaysia and other Asian countries.